2016
DOI: 10.1515/fhort-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of NANO-GRO® organic stimulator on the yielding and fruit quality of field tomato (Lycopersicon esculentum Mill.)

Abstract: The effect of different methods of NANO-GRO ® application on tomato plant growth and yield and its quality was determined. Four treatments were used: soaking seeds with NANO-GRO ® , plants spraying, double application: soaking seeds + plants spraying and a control without NANO-GRO ® . The cultivar Mieszko F 1 was used for the study. A significant influence of NANO-GRO ® application method on tomato plant growth, yield and quality was observed. Pre-sowing application positively influenced plant height and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Statistically significant differences between the cultivars were reported in 2011 and 2012, whereas in 2013, the marketable yield of all cultivars maintained on the same level. In the conducted research, the tomato fruit yield was similar or greater in comparison to other industrial cultivars examined in the climatic conditions of Poland [Kosterna 2014, Jędrszczyk andAmbroszczyk 2016]. In the most favorable year 2012, the mean marketable fruit yield of Awizo F 1 amounted to 95.64 t•ha -1 and it constituted 89% of the total yield.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Statistically significant differences between the cultivars were reported in 2011 and 2012, whereas in 2013, the marketable yield of all cultivars maintained on the same level. In the conducted research, the tomato fruit yield was similar or greater in comparison to other industrial cultivars examined in the climatic conditions of Poland [Kosterna 2014, Jędrszczyk andAmbroszczyk 2016]. In the most favorable year 2012, the mean marketable fruit yield of Awizo F 1 amounted to 95.64 t•ha -1 and it constituted 89% of the total yield.…”
Section: Resultsmentioning
confidence: 58%
“…5). In the research conducted by Jędrszczyk and Ambroszczyk [2016], in the fruits of an industrial tomato cultivar, the mean percent content of dry mass amounted to 5.79%, reducing sugars in total -2.27%, and vitamin C -19.83 mg•100 g -1 f.m. George et al [2004] report the content of vitamin C in various examined tomato cultivars between 8.4 and 30.4 mg•100 g -1 f.m., whereas Pavlović et al [2017] determined much lower values: 1.86-8.05 mg•100 g -1 f.m.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, in plant production systems, plants need to be assisted by using stimulators . Recently, many studies have been conducted on plants using nano‐stimulators, which can be natural plant extracts, chemical or a combination of both . They can also be nano‐metals or nanocomposites.…”
Section: Influence Of Nps On Abiotic Stress Resistance Of Plantsmentioning
confidence: 99%
“…However, this approach is not enough when the plant growth and development were processed under different stress factors such as hot or cold temperature, salinity, drought etc. A large body of publications in the world [5][6][7][8][9][10][11][12][13][14] showed the necessity to extend the chemical composition of fertilizer formulations. That is, besides microelements, it is necessary to add bioactive substances (referred to as biostimulants) and plant protection agents to the seed treatment formulations [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The results proved that the applied factor significantly accelerated the germination rate and seedlings length in the initial growth phase, but these parameters were reduced at a later time compared with the control. The study of the effect of Nano-Gro stimulator on tomato plant [6] demonstrated a considerable difference in physical and biochemical properties (plant height, root and apical trunk diameters and fruit quality indices) between the Nano-Gro-treated tomato and the control. The research also indicated the fact that this difference gradually declined over time and disappeared after two years of experiment.…”
Section: Introductionmentioning
confidence: 99%